Oracle RMAN for Absolute Beginners - Kuhn, Darl (Apress : Imprint: Apress, 2014)
Oracle RMAN for Absolute Beginners is a gentle introduction to the use of Oracle's Recovery Manager software to make backups of an Oracle database, and to restore all or part of a database in the event that data loss occurs. It is often said that a database administrator's #1 job responsibility is to be able to recover from data loss. If you're new to the Oracle platform, or you're new to database administration in general, you can hardly go wrong by making it your first priority to learn to backup and recover the database that has been entrusted into your hands. This book is short and sweet at just 200 pages. Focus lies on the mainstream use cases. Recovery Manager, or RMAN as it is called, is a powerful and complex tool that can be intimidating at first. Author Darl Kuhn understands the need to focus on the core use cases, building your confidence in the tool, and in your ability to recover from lost database files, and even to recover your entire database should that become necessary. Oracle RMAN for Absolute Beginners shows how to backup your database. That's the first job. You'll learn to backup the entire database, and to create incremental backups that in turn can speed restore and recovery operations. Then you'll learn to recover from lost data files, lost redo log files, lost control files, and even to restore the entire database from scratch. You'll even learn how to clone a database for development and test purposes by backing the database up on one system and restoring it onto another. Author Darl Kuhn has a decade and a half of experience in writing about, and teaching Oracle Database backup and recovery. If you are newly responsible for an Oracle Database, you can hardly do better than to pick up a copy of Oracle RMAN for Absolute Beginners.